Contamination and distribution of heavy metals, polybrominated diphenyl ethers and alternative halogenated flame retardants in a pristine mangrove. Issue 1 (15th February 2016) - Wu, Qihang; Leung, Jonathan Y.S.; Tam, Nora F.Y.; Peng, Yisheng; Guo, Pengran; Zhou, Song; Li, Qing; Geng, Xinhua; Miao, Shenyu
Abstract: Owing to the expanding metal and electronics industries, pollution in the Pearl River Estuary needs special concern. Given the hydrodynamic effect, the pristine mangrove in Qi'ao Island would be contaminated by tidal flushing. Thus, we examined (1) the contamination of pollutants in this mangrove, including heavy metals, polybrominated diphenyl ethers (PBDEs) and alternative halogenated flame retardants (AHFRs), and (2) how habitat characteristics and sediment properties affect their distribution. Results showed that the sediment in Qi'ao mangrove had higher concentrations of heavy metals, PBDEs and AHFRs than that in other pristine mangroves, and similar concentrations to those mangroves impacted by point sources. Heavy metal concentrations were lower in the vegetated areas than mudflat, while the opposite was found for PBDEs and AHFRs. The findings imply that tidal flushing was an important pollution source, while mangrove plants have the capacity to minimize the impact of heavy metals, but not PBDEs and AHFRs. Highlights: Concentrations of heavy metals, PBDEs and AHFRs were examined in a pristine mangrove. Sediment was contaminated by these pollutants, especially PBDEs and AHFRs. Tidal flushing was an important source of pollution. Mangrove plants could minimize the impact of heavy metals, but not PBDEs and AHFRs.